New Records of Katydids of the Genus Quiva (Orthoptera: Tettigoniidae: Phaneropterinae) to Brazil - Sovano, Rafael Segtowick (2013)
This paper reports a new record of Quiva diaphana Hebard and Quiva pulchella Rehn to Brazil along with the occurrence of Quiva abacata (Brunner von Wattenwyl) for the first time in the Brazilian Amazon, including distribution notes. Novos Registros de Esperanças do Gênero Quiva (Orthoptera: Tettigoniidae: Phaneropterinae) para o Brasil Resumo. Este trabalho reporta novos registros de ocorrência de Quiva diaphana Hebard e Quiva pulchella Renh para o Brasil, juntamente com a ocorrência de Quiva abacata (Brunner von Wattenwyl) pela primeira vez para a Amazônia brasileira, incluindo notas de distribuição.